Characterization of the Interactions between Endocrine Disruptors and Aquatic Humic Substances from Tropical Rivers - Botero, Wander G.; de Oliveira, Luciana C.; Cunha, Bruno B. [UNESP]; de Oliveira, Lilian K. [UNESP]; Goveia, Danielle [UNESP]; Rocha, Julio Cesar [UNESP]; Fraceto, Leonardo F. [UNESP]; Rosa, André Henrique [UNESP] (Soc Brasileira Quimica, 2011)
Interactions between two endocrine disruptors (ED) and aquatic humic substances (AHS) from tropical rivers were studied using an ultrafiltration system equipped with a 1 kDa cut-off cellulose membrane to separate free ED from the fraction bound in the AHS. Quantification of 17 alpha-ethynylestradiol and bisphenol A was performed using gas chromatography-mass spectrometry (GC-MS). The times required for establishment of equilibrium between the AHS and the ED were ca. 30 min, and complexation capacities for 17 alpha-ethynylestradiol and bisphenol A were 18.53 and 2.07 mg g(-1) TOC, respectively. The greater interaction of AHS with 17 alpha-ethynylestradiol, compared to bisphenol A, was due to the presence of hydrogen in the structure of 17 alpha-ethynylestradiol, which could interact with ionized oxygenated groups of the AHS. The results indicate that AHS can strongly influence the transport and reactivity of endocrine disruptors in aquatic systems.
Keywords: water; pollution; endocrine disruptors; aquatic humic substances; complexation capacity